1989
DOI: 10.2514/3.10211
|View full text |Cite
|
Sign up to set email alerts
|

Flow structure and scaling laws in lateral wing-tip blowing

Abstract: When a thin jet sheet exits from the tip of a straight wing in the spanwise direction, the wing experiences a lift augmentation. In many cases, lateral blowing causes a lateral displacement of the tip vortices, without complicating the vortex structure. In such cases, simple scaling laws for blowing intensity and lift augmentation have been found to hold. However, in some instances blowing also produces secondary vortices, which sometimes are associated with a breakdown of the scaling laws. Flow surveys for se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…Hence, the modeled slot width is set to the characteristic length scale of the discrete delta function, x 0:04c. Compared with the typical slot widths of =c 0:01 used in flow control [31][32][33], the current slot width in our simulations is slightly larger. Nonetheless, the present forcing function is used to explore control techniques at this low Reynolds number.…”
Section: Controlled Flow Actuator Modelmentioning
confidence: 85%
“…Hence, the modeled slot width is set to the characteristic length scale of the discrete delta function, x 0:04c. Compared with the typical slot widths of =c 0:01 used in flow control [31][32][33], the current slot width in our simulations is slightly larger. Nonetheless, the present forcing function is used to explore control techniques at this low Reynolds number.…”
Section: Controlled Flow Actuator Modelmentioning
confidence: 85%
“…Using steady air blowing at the tip to perturb the forming vortex is an attractive strategy because of the availability of engine bleed air used for wing de-icing at cruise. Previous studies 8,9,10,11 have all shown that spanwise blowing from slots in the wing tip can improve the wing's aerodynamic performance by creating an effective increase in aspect ratio with the by-product that the tip vortex is pushed outwards and generally upwards. The results showed a great sensitivity of the near field to the blowing configuration and blowing coefficient, whereas, some configurations resulted in a more coherent structure of the vortex.…”
Section: Introductionmentioning
confidence: 98%
“…The typical active control of wing tip vortex is by way of blowing or sucking in the wing tip. Lee et al [8,9] showed that a lateral blowing might generate a secondary vortex at a certain instance, and the displacement of vortex depends on the different ways of blowing, that is, blowing angle, blowing, and flux. Margaris and Gursul [10] conducted their experiment on a rectangular wing using different blowing slots and found that blowing toward the lower surface of the wing could produce a pair of co-rotating vortex, which accelerated the dissipation of vortices and decreased the induced drag.…”
Section: Introductionmentioning
confidence: 99%